Foot pod technology and their utility for change of direction testing: a technological review - Albarrán, E. J.; Cronin, J. (Strength and Conditioning Journal, 2025)
The integration of technology into strength and conditioning practice is burgeoning, with the choices available to the practitioner somewhat overwhelming. Foot pods are one such technology and certainly deserve a place in the strength and conditioning coach's toolbox; therefore, their capability and utility needs to be understood. The focus of this review is to evaluate the inertial measurement unit and accelerometer technology located at the foot or ankle and assess their potential to provide appropriate metrics and information that could assist in interpreting change of direction (COD) performance. This review will briefly summarize the potential uses of the foot pod technology and what metrics it can provide in reference to COD testing and then review the foot pods that are on the market, specifically their specifications, what they measure, the status of reliability or validity research associated with the product, and list some of the advantages and disadvantages associated with each technology.